Modulation of dietary protein to lipid ratios for gilthead seabream on-growing during summer temperature conditions - Aragão, Cláudia (2022)
Gilthead seabream (Sparus aurata) tend to increase fat deposition during summer farming conditions in the Mediterranean, which may negatively affect productive performance and consumers' quality perception of the final product. Therefore, this study evaluated the impacts of protein to lipid ratios in low fishmeal/fish oil diets on growth performance, body composition, feed conversion and nutrient utilization of seabream on-grown during summer temperature conditions. The experimental diets contained low levels of fishmeal, fish oil, and crude protein (39%), differing in crude lipid content: 16% (MF diet) or 12% (LF diet). A growth trial was per-formed with seabream (initial weight: 100 & PLUSMN; 7 g) from August to October (water temperature: 23.1 & PLUSMN; 2.2 & DEG;C). A digestibility trial was also performed (at 23 & DEG;C). Key performance indicators, whole-body composition and ac-tivities of digestive enzymes were evaluated at the end of the experiment (64 days). Low dietary lipid levels negatively affected lipid, energy, and amino acid digestibility, and as a result, fish fed the LF diet presented higher nitrogen faecal losses. Still, the decrease in nutrient digestibility was not related to dietary effects on the digestive enzyme activities. The experimental diets did not compromise the activity of pancreatic, gastric, and intestinal digestive enzymes nor feed utilization, but a slight growth impairment was observed in fish fed the LF diet, probably due to the lower amino acid and lipid digestibility. However, a potential benefit of this dietary treatment towards reducing fat accumulation in seabream during summer was observed. Nevertheless, the environmental impact of the nitrogen losses during seabream on-growing should be considered when estimating the sustainability of the production. This study demonstrated that the optimisation of diet formulations should account for the environmental conditions, especially in Mediterranean aquaculture, so the economic and envi-ronmental impacts may be correctly evaluated towards a more sustainable fish production.